2020
DOI: 10.2147/dmso.s267122
|View full text |Cite
|
Sign up to set email alerts
|

<p>Joint Effects of Plasma Homocysteine Concentration and Traditional Cardiovascular Risk Factors on the Risk of New-Onset Peripheral Arterial Disease</p>

Abstract: Purpose: Hyperhomocysteinemia is an independent risk factor for cardio-and cerebrovascular diseases. However, the relationship between plasma homocysteine (Hcy) concentration and peripheral arterial disease (PAD) has not been completely characterized. The aim of the present study was to determine the relationship between plasma Hcy concentration and new-onset PAD and to assess the effects of combinations of Hcy and traditional cardiovascular risk factors. Patients and Methods: We conducted a prospective commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…[ 8 ] H-type hypertension influences BP and cardiovascular health outcomes. [ 20 , 21 ] Other studies have highlighted that MTHFR C677T genotyping is important. [ 22 , 23 ] In a recent study of hypertension, hypertension in a small population of people was found to be related to a prothrombotic state, [ 24 ] which suggests that the prothrombotic state is a negative influencing factor in hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] H-type hypertension influences BP and cardiovascular health outcomes. [ 20 , 21 ] Other studies have highlighted that MTHFR C677T genotyping is important. [ 22 , 23 ] In a recent study of hypertension, hypertension in a small population of people was found to be related to a prothrombotic state, [ 24 ] which suggests that the prothrombotic state is a negative influencing factor in hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The mean serum Hcy was 20.50 (13.64) μmol/L and 15.77 (7.35) μmol/L among males and females, respectively. Recent studies have shown that hyperhomocysteinemia is associated with an increased risk of PAD ( Liu et al, 2020 ). Hyperhomocysteinemia can directly or indirectly produce toxic effects on vascular endothelial cells by damaging vascular endothelial cells, promoting platelet activation, enhancing coagulation, producing cytotoxic reactive oxygen species, reducing antioxidation and proliferation of vascular smooth muscle cells, thus promoting atherosclerosis ( Liu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that hyperhomocysteinemia is associated with an increased risk of PAD ( Liu et al, 2020 ). Hyperhomocysteinemia can directly or indirectly produce toxic effects on vascular endothelial cells by damaging vascular endothelial cells, promoting platelet activation, enhancing coagulation, producing cytotoxic reactive oxygen species, reducing antioxidation and proliferation of vascular smooth muscle cells, thus promoting atherosclerosis ( Liu et al, 2020 ). According to previous studies, bilirubin is an antioxidant that can prevent atherosclerosis, but there is no study on the pathological mechanism between bilirubin and homocysteine.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, using de nite cut-off values of Hcy concentration de ned by guidelines or previous classical studies for risk strati cation may underestimate the actual risk of patients. In addition, because homocysteine and hypertension have a synergistic effect on the prognosis of cardiovascular disease [9], homocysteine may have different effects on prognosis of ACS patients with complicated hypertension or not. As a result, we divided ACS patients into hypertension and non-hypertension groups and used ROC analysis to determine the optimal critical value of homocysteine for predicting long-term death in ACS patients in each of the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the increase in Hcy level is strongly associated with the occurrence and development of hypertension by inhibiting endogenous hydrogen sul de generation and activating angiotensin-converting enzymes [7,8]. Meanwhile, [9,10] reported that hypertension and hyperhomocysteinemia have a signi cant synergistic effect on cardiovascular disease prognosis. Therefore, Hcy may have a different in uence on prognosis in hypertensive and non-hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%